Alterations in the surface features of S-doped carbon and g-C3N4 photocatalysts in the presence of CO2 and water upon visible light exposure. Issue 31 (17th May 2017) - Li, Wanlu; Hu, Yuping; Rodríguez-Castellón, Enrique; Bandosz, T. J.
Abstract : The surfaces of g-C3 N and S-doped carbons upon exposure to water and/or CO2 under visible light are oxidized as a result of photoactivity and chemical reactivity. Abstract : Graphitic carbon nitride and S-doped carbon catalysts were exposed to CO2 and/or water either in the dark or under visible light irradiation. The surface chemistry of the initial and exposed samples was studied by XPS and potentiometric titration. In the case of porous carbon catalysts the changes in porosity were also estimated based on the adsorption of nitrogen. The results showed that exposure to water and CO2 caused changes in its surface chemistry. The changes were especially pronounced when the surfaces were exposed to CO2 under visible light irradiation. Mainly, oxidation of surface carbon atoms was observed, which was accompanied by the reduction of surface nitrogen in the case of g-C3 N4, and removal of some sulfur species in the case of S-doped carbons. These changes were the consequence of photosensitivity and the oxidation of water and reduction of CO2 . Moreover, the chemical reactivity of water and CO2 was also noticed in the dark, which was linked to hydrolysis and redox reactions, respectively. The changes in the chemistry were apparently affected by the extent of photoactivity and surface reactions, the amount of generated oxygen and the reactivity of the surface atoms. The results showed small but consistent changes in the chemistry and texture of catalysts, which might affect their applications.